Influence of Compensation Procedural Fairness and Employee Engagement on Workforce Agility and Its Impact on Employee Performance - Dwi Ardian; Nurhayati , Mafizatun; Madris, Madris (International Journal of Applied Management and Business, 2023)
Purpose – The objective of the research is to examine the influence of compensation procedural fairness and employee engagement on workforce agility and its impact on employee performance at BPS Sulawesi Barat Province. Methodology/approach – The causality associative research approach is used in this research design. The Structural Equation Modeling with Partial Least Square (SEM-PLS) approach is used in this study for quantitative analysis, while graphs and tables are used for descriptive analyses. The primary data used in this study was obtained from 139 respondents throughout the entire BPS Sulawesi Barat Province's units. Findings – The findings imply that compensation procedural fairness and employee engagement have significant effects on employee performance. Additionally, fairness in the compensation procedure and employee engagement through workforce agility substantially impact employee performance. Meanwhile, compensation procedural fairness was found to have no direct significant impact on employee performance. These findings differ from previous studies. Novelty/value – BPS Vision as the quality data provider for advanced Indonesia, must ensure the fulfilment of the demand of data users. In addition, the volatility, uncertainty, complexity, and ambiguity (VUCA) conditions of the workplace made employee engagement, workforce agility, and compensation procedural fairness necessary to respond to challenges. This study is particularly new in government data provider organisations; therefore, the conclusions are crucial for planning and evaluation.